Maritime Insecurities in the Sulu and Sulawesi Seas - Pradityo, Rahmadanu (Institut Teknologi Sepuluh Nopember, 2024)
The increase in the threat of crime in the Sulu and Sulawesi Seas in recent years has caused the countries bordering the two seas, namely Indonesia, Malaysia, and the Philippines, to agree to form a trilateral cooperation called INDOMALPHI in 2016. The 2017 attack on Marawi City, Philippines, by a group affiliated with an international terrorist network has added to the security vulnerabilities in the Sulawesi and Sulu Seas. Despite being constrained by the COVID-19 pandemic, trilateral cooperation continues with all its limitations, namely through online meetings. Until 2022, through the Ministry of Defense, the three countries will strengthen the trilateral cooperation agreed in Malaysia again. This study uses a maritime insecurity concept framework with a qualitative approach that uses a literature study data collection method consisting of books, journal articles, official ASEAN websites, and online news sites. The results of the study show that there are still threats that cause maritime insecurity, which encourages the strengthening of trilateral cooperation by Indonesia, Malaysia, and the Philippines in 2022 in order to realize maritime security in the Sulu and Sulawesi Sea regions.